Hot vulcanization adhesive containing microcapsule structure and preparation method of hot vulcanization adhesive
Through microencapsulation treatment of highly active substances, non-ionic and anionic dispersants are used to form microcapsule structures, solving the problem of poor storage performance of high-active vulcanized glues, improving aging resistance and storage stability, and being suitable for industrial production.
Patent Information
- Application Number
- CN202411261998.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-20
AI Technical Summary
The poor storage performance of highly active vulcanized glues leads to aging resistance deterioration. Existing methods such as reducing solid content, premixing and low-temperature storage increase production and storage costs.
Microencapsulation is used to treat highly active substances, and a microcapsule structure is formed by combining non-ionic and anionic dispersants to avoid the vulcanization reaction of active substances at room temperature, and improve the aging resistance of vulcanized glue.
It improves the aging resistance and storage stability of high-active vulcanized glue, avoids local gel formation, reduces storage failure, and is suitable for large-scale industrial production.
Smart Images

Figure BDA0005035983870000094 
Figure BDA0005035983870000101 
Figure HDA0005035983880000011
Abstract
Description
Technical Field
[0001] The invention relates to a heat-vulcanized adhesive containing a microcapsule structure and a preparation method thereof, and relates to C09J, in particular to the field of adhesives. Background Art
[0002] The bonding principle of hot-vulcanized adhesives is that under the conditions of heating and pressurization, cross-linking reactions occur simultaneously between the base glue and the adhesive, and between the base glue and the substrate, so that they are bonded into an integral part. With the increase in product performance requirements, the performance requirements for hot-vulcanized adhesives are getting higher and higher. In order to improve the performance of adhesives, highly active substances will be introduced during the development process to meet the requirements of harsh corrosion resistance, liquid resistance, heat resistance, high strength, and high hardness, but the introduction of highly active substances will cause the storage performance of the product to be substandard. Highly active substances will consume a part of the internal reaction before use, resulting in a partial decrease in the final performance of the product and a decrease in aging resistance. Existing methods for improving aging resistance include reducing solid content, producing A and B glues, and storing at low temperatures. However, reducing solid content requires changing the production line, A and B glues need to be pre-mixed, and low-temperature storage requires cold storage, which will increase storage costs and be inconvenient to use. The present application has developed a hot-vulcanized adhesive containing a microcapsule structure, which can overcome the technical problem of poor storage performance of highly active vulcanized rubber.
[0003] Chinese invention patent CN201310026430.6 discloses a hot-vulcanized adhesive for bonding vulcanized rubber or thermoplastic rubber to hard plates, containing mononitrosophenol-blocked toluene-2,4-diisocyanate, thereby avoiding the use of aromatic polynitroso compounds that are easily sublimated or highly toxic polyisocyanate monomers, and having the performance of "preheating resistance", but the yield of mononitrosophenol-blocked toluene-2,4-diisocyanate is not high, and the production process is cumbersome. Chinese invention patent CN202111487668.X discloses a repair mortar for tire vulcanization bladders and its preparation and use methods, wherein attapulgite and isocyanate-modified epoxy resin are mixed and stirred, and the isocyanate-modified epoxy resin is loaded on the surface and pores of the attapulgite, and then mixed with halogenated rubber as a filler, and the obtained repair mortar has high bonding strength, good high temperature resistance, good toughness, and good thermal conductivity, but poor aging resistance. Summary of the invention
[0004] In order to overcome the technical problem of poor storage performance of highly active vulcanized rubber, the first aspect of the present invention provides a hot-vulcanized adhesive containing a microcapsule structure, and the preparation raw materials include, by weight percentage: 2-15% halogen-containing polymer, 1-10% vulcanizing agent, 1-10% nitrogen-containing prepolymer, 1-10% reinforcing agent, 1-10% filler, 0.01-2% microcapsule packaging material, and xylene is supplemented to 100%.
[0005] As a preferred embodiment, the microcapsule packaging material comprises an aqueous phase and an organic phase, and the weight ratio of the aqueous phase to the organic phase is (1-2): (1-2).
[0006] As a preferred embodiment, the raw materials for preparing the water phase include water, a dispersant and a nitrogen curing agent, the dispersant accounts for 2%-5% of the mass of water, and the nitrogen curing agent accounts for 0.02-2% of the total mass of the heat-vulcanized adhesive.
[0007] As a preferred embodiment, the nitrogen curing agent is selected from one or a combination of adhesive RH, adhesive H (purchased from Jinan Zhengxing Rubber Additive Co., Ltd.), adhesive A (N-hexamethoxy-N-hydroxymethyl melamine), HTM, RA, resorcinol, RS, RE, R-8ORF, and RL.
[0008] As a preferred embodiment, the nitrogen curing agent is selected from one or a combination of adhesives RH, H, A, and resorcinol.
[0009] As a preferred implementation, the nitrogen-based curing agent is an adhesive RH.
[0010] As a preferred embodiment, the HLB value of the dispersant is greater than 10, and the dispersant is selected from a nonionic dispersant, an anionic dispersant, or a combination of both.
[0011] As a preferred embodiment, the nonionic dispersant is selected from one or a combination of polyoxyethylene castor oil, nonylphenol polyoxyethylene, peregal 10, Tween-20, Tween-40, Tween-60, Tween-80, and polyvinyl alcohol.
[0012] As a preferred embodiment, the anionic dispersant is selected from one or a combination of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, and potassium oleate.
[0013] As a preferred embodiment, the dispersant is a combination of a nonionic dispersant and an anionic dispersant, and the weight ratio of the nonionic dispersant to the anionic dispersant is (0.4-0.9):0.1.
[0014] As a preferred embodiment, the dispersant is a combination of sodium dodecyl sulfate and polyvinyl alcohol, and the weight ratio of the sodium dodecyl sulfate to the polyvinyl alcohol is 0.6:0.1.
[0015] The applicant found in the experiment that the highly active substances in the vulcanized rubber are microencapsulated so that the active substances do not contact each other at room temperature, avoid the vulcanization reaction of the active substances at room temperature, and make the active substances react as much as possible when used, thereby improving the aging resistance of the highly active vulcanized rubber. The applicant further found in the experiment that the aqueous phase of the formed capsule structure needs to be used in combination with nonionic and anionic dispersants to achieve a good capsule coating effect, and the weight ratio of the anionic dispersant to the nonionic dispersant is (0.4-0.9): 0.1 to achieve a good aging resistance effect. It is speculated that the possible reason is that the cross-linked structure gap of the formed capsule structure is larger when the anionic dispersant and the nonionic dispersant exceed the preferred weight ratio, and the highly active powder will pass through the capsule wall, the active substance will be exposed, and a partially solidified gel will appear at room temperature, thereby reducing the aging resistance effect.
[0016] As a preferred embodiment, the raw materials for preparing the organic phase include an organic solvent, a microcapsule wall material, a thermal initiator and a photoinitiator, and the microcapsule wall material accounts for 2%-5% of the mass of the organic solvent.
[0017] As a preferred embodiment, the organic solvent is selected from one or a combination of xylene or methyl isobutyl ketone.
[0018] As a preferred embodiment, the thermal initiator includes but is not limited to AIBN (azobisisobutyronitrile), ABVN (azobisisoheptanenitrile), V601 (cyclic azo amidine initiator), and AIBME (dimethyl azobisisobutyrate) initiator.
[0019] As a preferred embodiment, the photoinitiator includes but is not limited to diaryliodonium salt I-250, TPO (2,4,6-trimethylbenzoyl-diphenylphosphine oxide), 1173 (2-hydroxy-2-methyl-1-phenylpropanone), 184 (1-hydroxycyclohexylphenylketone), 907 (2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone), 659 (2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone) photoinitiator.
[0020] As a preferred embodiment, the microcapsule wall material is selected from one or a combination of methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methylpropionate, butyl methylpropionate, styrene, dimethyl carbonate, and methacrylic acid.
[0021] As a preferred embodiment, the microcapsule wall material is a combination of dimethyl carbonate, methyl methacrylate, styrene and methacrylic acid.
[0022] As a preferred embodiment, the weight ratio of dimethyl carbonate, methyl methacrylate, styrene and methacrylic acid is 1:(0.1-0.2):(0.1-0.2):(0.01-0.1).
[0023] As a preferred embodiment, the weight ratio of dimethyl carbonate, methyl methacrylate, styrene and methacrylic acid is 1:0.15:0.1:0.05.
[0024] As a preferred embodiment, the halogen-containing polymer is a halogenated rubber, and the halogenated rubber is selected from one or a combination of chlorosulfonated polyethylene, chlorinated natural rubber, chlorinated polypropylene, maleic anhydride modified chlorinated polypropylene, epoxy resin modified chlorinated polypropylene, chlorinated ethylene-vinyl acetate copolymer, and chlorinated polyethylene.
[0025] As a preferred embodiment, the halogen-containing polymer is a combination of chlorosulfonated polyethylene and maleic anhydride-modified chlorinated polypropylene.
[0026] As a preferred embodiment, the weight ratio of the chlorosulfonated polyethylene to the maleic anhydride modified chlorinated polypropylene is (5-7): (3-5).
[0027] As a preferred embodiment, the weight ratio of the chlorosulfonated polyethylene to the maleic anhydride modified chlorinated polypropylene is 6:3.5.
[0028] As a preferred embodiment, the vulcanizing agent is selected from one or a combination of p-benzoquinone dioxime, vulcanizing agent DGM (dibenzoylquinone dioxime), tetrachloro-p-benzoquinone, accelerator NS (N-tert-butyl-2-benzothiazole sulfenamide), accelerator DIBS (N,N'-diisopropyl-2-benzothiazole sulfenamide), accelerator CZ (N-cyclohexyl-2-benzothiazole sulfenamide), accelerator NOBS (N-(diethylene oxide)-2-benzothiazole sulfenamide), and accelerator AZ (diethylbenzothiazole sulfenamide).
[0029] As a preferred embodiment, the vulcanizing agent is p-benzoquinone dioxime.
[0030] As a preferred embodiment, the nitrogen-containing prepolymer is selected from one or a combination of N,N'-m-phenylene bismaleimide, N,N'-4,4'-diphenylmethane bismaleimide, 1,11-bis(maleimido)-3,6,9-trioxaundecane, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, and 1,2-dimaleimidoethane.
[0031] As a preferred embodiment, the nitrogen-containing prepolymer is N,N'-m-phenylene bismaleimide prepolymer.
[0032] As a preferred embodiment, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane prepolymer is preferably used when bonding EPDM rubber and butyl rubber.
[0033] As a preferred embodiment, the weight average molecular weight of the nitrogen-containing prepolymer is 350-20000, preferably, the weight average molecular weight of the nitrogen-containing prepolymer is 350-9000, and more preferably, the weight average molecular weight of the nitrogen-containing prepolymer is 2000.
[0034] As a preferred embodiment, the reinforcing agent is selected from one or a combination of carbon black or fumed silica.
[0035] As a preferred embodiment, the carbon black is selected from one or a combination of Cabot N550, Cabot 774, and Cabot 762.
[0036] As a preferred embodiment, the fumed silica is selected from one or a combination of Degussa A200 and Cabot R972.
[0037] As a preferred embodiment, the filler includes but is not limited to one or a combination of fly ash, mica powder, zinc oxide, and selenium powder.
[0038] As a preferred embodiment, the initial particle size of the halogen-containing polymer, vulcanizing agent, nitrogen-containing prepolymer, reinforcing agent, and filler is 0.02-500 μm, and the particle size after processing is 0.02-40 μm.
[0039] As a preferred embodiment, the hot-vulcanized adhesive containing the microcapsule structure has a viscosity of 100-1000 cps and a density of 935-1150 g / cm at 25°C and 2# rotor 30 rpm. 3 , solid content 20-50wt%, flash point -5~30℃.
[0040] A second aspect of the present invention provides a method for preparing a heat-vulcanized adhesive containing a microcapsule structure, comprising the following steps:
[0041] S1 weighs the crushed halogen polymer and dissolves it in xylene to form a glue solution for later use;
[0042] S2 weighs sulfide, nitrogen-containing prepolymer, reinforcing agent, and filler and disperses them in xylene, then adds the prepared glue solution, stirs and disperses them in a stainless steel container, and then grinds them with a sand mill to control the fineness, discharges the material, obtains a mother liquor, and sets it aside;
[0043] S3: adding a dispersant and a nitrogen curing agent to water, dispersing and dissolving them to obtain a water phase; adding a wall material, a thermal initiator and a photoinitiator to an organic solvent, dispersing and dissolving them to obtain an organic phase;
[0044] S4: gradually drop the organic phase into the aqueous phase, emulsify while stirring, initiate polymerization using a light curing machine after the dropwise addition, precipitate a white precipitate after irradiation, centrifuge, wash, dry, and sieve to obtain a microcapsule structure;
[0045] S5: dispersing the microcapsule structure into the mother solution prepared in step S2, adding xylene, and dispersing the microcapsule structure uniformly.
[0046] As a preferred embodiment, the total grinding time in step S2 is 30-60 min, the number of grindings is 2-3 times, and the fineness of the mother liquor is ≤45 μm.
[0047] As a preferred embodiment, the total grinding time in step S2 is 45 minutes, the grinding times are 2-3 times, and the fineness of the mother liquor is ≤45 μm.
[0048] As a preferred embodiment, the stirring and dispersing speed in step S2 is 500-700 r / min, and the dispersing time is 1-3 h.
[0049] As a preferred embodiment, the stirring and dispersing speed in step S2 is 600 r / min and the dispersing time is 2 h.
[0050] As a preferred embodiment, in step S4, the stirring speed is 30000-40000 r / min, and the dropping speed of the organic phase is 5-15 mL / s.
[0051] As a preferred embodiment, in step S4, the stirring speed is 35000 r / min, and the dropping speed of the organic phase is 10 mL / s.
[0052] As a preferred implementation, in step S4, the power of the light curing machine is ≥1 kW, and the irradiation time is 10-60 min.
[0053] As a preferred implementation, in step S4, the power of the light curing machine is ≥1 kW, and the irradiation time is 45 minutes.
[0054] As a preferred embodiment, in step S4, the centrifugal speed is 8000-12000 r / min, the drying temperature is 30-90° C., the drying time is 0.5-1.5 h, and the product is sieved through a 400-mesh sieve.
[0055] As a preferred embodiment, in step S4, the centrifugal speed is 10000 r / min, the drying temperature is 60° C., the drying time is 1 h, and the product is sieved through a 400-mesh sieve.
[0056] As a preferred embodiment, in step S5, the dispersion speed is 300-800 r / min, and the dispersion time is 0.5-1.5 h.
[0057] As a preferred implementation, in step S5, the dispersion speed is 600 r / min and the dispersion time is 1 h.
[0058] Compared with the prior art, the present invention has the following beneficial effects:
[0059] (1) The hot-vulcanized adhesive containing a microcapsule structure of the present invention uses microencapsulation to treat the highly active substances in the vulcanized rubber, thereby avoiding the vulcanization reaction of the active substances at room temperature and improving the aging resistance of the highly active vulcanized rubber.
[0060] (2) The heat-vulcanized adhesive containing a microcapsule structure of the present invention can achieve a good capsule coating effect by using a combination of nonionic and anionic dispersants in the water phase of the microcapsule structure, thereby improving the storage stability of the vulcanized adhesive.
[0061] (3) The heat-vulcanized adhesive containing a microcapsule structure of the present invention has a nonionic dispersant and an anionic dispersant in a weight ratio of 0.1:(0.4-0.9) in the microcapsule structure, which can avoid local gelation at room temperature and avoid storage failure of highly activated vulcanized rubber.
[0062] (4) The hot-vulcanized adhesive containing a microcapsule structure of the present invention is microencapsulated after introducing active groups such as amino, hydroxyl, and isocyanate groups. The encapsulated active substances can be released by breaking the shell at high temperatures to achieve a bonding effect, thereby solving the problem of extremely short product storage period.
[0063] (5) The heat-vulcanized adhesive containing a microcapsule structure of the present invention solves the storage stability and aging resistance problems of heat-vulcanized adhesives with ammonia and isocyanate groups added to the formula, and does not require additional production costs, so it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a schematic diagram of the heat-vulcanized adhesive prepared in Example 3 after aging. DETAILED DESCRIPTION
[0065] Example 1
[0066] A heat-vulcanized adhesive containing a microcapsule structure, wherein the raw materials for preparation include: 9.5 kg of halogen-containing polymer, 6 kg of vulcanizing agent, 2 kg of nitrogen-containing prepolymer, 3.65 kg of reinforcing agent, 3.2 kg of filler, microcapsule packaging material, and xylene.
[0067] The halogen-containing polymer is a combination of chlorosulfonated polyethylene and maleic anhydride-modified chlorinated polypropylene, with a weight ratio of 6:3.5. The chlorosulfonated polyethylene was purchased from Jilin Petrochemical, with a brand of 3305; the maleic anhydride-modified chlorinated polypropylene was purchased from Shanghai Pulitong New Material Technology Co., Ltd., with a brand of CPPg565.
[0068] The vulcanizing agent is p-benzoquinone dioxime;
[0069] The nitrogen-containing prepolymer is N,N'-m-phenylene bismaleimide prepolymer with a weight average molecular weight of 2000, which is purchased from Shanghai Pulitong New Material Technology Co., Ltd.
[0070] The reinforcing agent includes 2.8 kg of N550 carbon black, 0.7 kg of N774 carbon black and 0.15 kg of A200 fumed silica, wherein N550 and N774 are purchased from Cabot, and A200 is purchased from Degussa.
[0071] The filler includes 1 kg of mica powder, 2 kg of zinc oxide, and 0.2 kg of selenium powder; the mica powder is purchased from Lingshou County Dongfeng Mineral Processing Plant, the zinc oxide is purchased from Anqiu Hengshan Zinc Industry, and the selenium powder is purchased from Xiangtan County Jurong Technology Co., Ltd.
[0072] The microcapsule packaging material includes an aqueous phase and an organic phase, wherein the aqueous phase is 21.7 kg and the organic phase is 10 kg.
[0073] The raw materials for preparing the water phase include 20 kg of water, 0.7 kg of dispersant and 1 kg of nitrogen-based curing agent.
[0074] The dispersant is a combination of sodium dodecyl sulfate and polyvinyl alcohol, with a weight ratio of 0.6:0.1. The polyvinyl alcohol is PVA1799 purchased from Jinan Weixing Chemical.
[0075] The nitrogen-based curing agent is adhesive RH, purchased from Jiangsu Guoli Chemical Technology Co., Ltd.
[0076] The raw materials for preparing the organic phase include 9 kg of organic solvent, 1.3 kg of microcapsule wall material, 7.5 g of thermal initiator and 2 g of photoinitiator.
[0077] The organic solvent is xylene. The thermal initiator is AIBN, and the photoinitiator is a combination of TPO and 1173, with a weight ratio of 1:1.
[0078] The microcapsule wall material is a combination of 1 kg dimethyl carbonate, 0.15 kg methyl methacrylate, 0.1 kg styrene and 0.05 kg methacrylic acid.
[0079] A method for preparing a heat-vulcanized adhesive containing a microcapsule structure comprises the following steps:
[0080] S1 weighs the crushed halogen polymer and dissolves it in 43.86 kg of xylene to form a glue solution for later use;
[0081] S2 weighs sulfide, nitrogen-containing prepolymer, reinforcing agent, and filler and disperses them in 25 kg of xylene, then adds 10 kg of the prepared glue, stirs and disperses them in a 304 stainless steel cylinder with 100 kg of solvent, and then grinds them in a 3L sand mill with a filling rate of 50%, controls the fineness, discharges the material, obtains the mother liquor, and sets it aside;
[0082] S3: adding a dispersant and a nitrogen curing agent to water, dispersing and dissolving them to obtain a water phase; adding a wall material, a thermal initiator and a photoinitiator to an organic solvent, dispersing and dissolving them to obtain an organic phase;
[0083] S4: 10 kg of organic phase is gradually added dropwise to the aqueous phase, emulsified while stirring, and after the addition is completed, polymerization is initiated by a light curing machine, and a white precipitate is precipitated after irradiation, centrifuged, washed, dried, and sieved to obtain a microcapsule structure;
[0084] S5: Disperse the microcapsule structure into the mother solution prepared in step S2, add 18.95 kg of xylene, make the weight 100 kg, and disperse evenly.
[0085] The total grinding time in step S2 is 45 minutes, the grinding times are 2-3 times, the fineness of the mother liquid is ≤45 μm, the stirring and dispersing speed is 600 r / min, and the dispersing time is 2 hours.
[0086] In step S4, the stirring speed is 35000 r / min, the dripping speed of the organic phase is 10 mL / s, the power of the light curing machine is ≥1 kW, the irradiation time is 45 min, the centrifugal speed is 10000 r / min, the drying temperature is 60°C, the drying time is 1 h, and the mixture is sieved through a 400 mesh screen.
[0087] In step S5, the dispersion speed is 600 r / min and the dispersion time is 1 h.
[0088] Example 2
[0089] A heat-vulcanized adhesive containing a microcapsule structure, the specific implementation manner is the same as that of Example 1, except that the raw materials for preparing the water phase include 20 kg of water, 0.4 kg of a dispersant and 1 kg of a nitrogen-based curing agent.
[0090] The dispersant is a combination of sodium dodecyl sulfate and polyvinyl alcohol, with a weight ratio of 0.3:0.1. The polyvinyl alcohol is PVA1799 purchased from Jinan Weixing Chemical.
[0091] Example 3
[0092] A heat-vulcanized adhesive, wherein the raw materials for preparation include: 9.5 kg of halogen-containing polymer, 6 kg of vulcanizing agent, 2 kg of nitrogen-containing prepolymer, 3.65 kg of reinforcing agent, 3.2 kg of filler, and xylene.
[0093] The specific selection and addition amount of raw materials are the same as in Example 1.
[0094] A method for preparing a heat-vulcanized adhesive comprises the following steps:
[0095] S1 weighs the crushed halogen polymer and dissolves it in 43.86 kg of xylene to form a glue solution for later use;
[0096] S2 weighs sulfide, nitrogen-containing prepolymer, reinforcing agent, and filler and disperses them in 25kg of xylene, then adds 10kg of the prepared glue, stirs and disperses them in a 304 stainless steel cylinder with 100kg of solvent, and then grinds them in a 3L sand mill with a filling rate of 50%. Control the fineness and discharge the material to obtain S2.
[0097] Performance Testing
[0098] 1. Aging performance test: The samples of Examples 1-3 were placed in a special explosion-proof galvanized iron can, placed in a 50.0°C oven, aged for 42 days, which is equivalent to being parked at 25°C for 365 days, and the sample status was observed. The test results are shown in Table 2. The effect diagram of the hot vulcanized adhesive of Example 3 after aging is shown in Table 2. Figure 1 .
[0099] 2. Adhesion test: Refer to ASTM D429-2014 standard, use method B, 90° peeling method.
[0100] The bonding requirements are as follows:
[0101] Adhesive coating requirements: Apply primer with a thickness of 5-12 μm on the T2 steel plate stamping strip, then apply the hot-vulcanized adhesive prepared in Example 1-2 and the aged adhesive of Example 1-2, with a total thickness of 25-35 μm, and then vulcanize after combining with rubber.
[0102] Use Wuxi Yangming JD-RL200 injection molding machine to vulcanize the glue combination: Application Example 1: Base glue: commodity 815GB; Adhesive of Example 1;
[0103] Application Example 2: Primer: Commodity 815GB; Adhesive of Example 2;
[0104] Application Example 3: Primer: Commodity 815GB; Adhesive of Example 3;
[0105] Vulcanization conditions: injection vulcanization at 160℃ in the cavity for 7min, molding pressure 16MPa, molding thickness 3mm thin sheet. Injection process: time 30s, feed pressure 160kg / cm 2 The test results are shown in Table 3.
[0106] The natural rubber is Yunnan No. 5 standard rubber purchased from Yunnan Agricultural Reclamation Group; the butadiene rubber is purchased from TSRC-UBE with the brand name BR0150; the coumarone resin is purchased from Puyang Hengtai Petrochemical Co., Ltd. with the brand name M1100.
[0107] The rubber formula is as shown in Table 1:
[0108] Table 1
[0109]
[0110]
[0111] Table 2
[0112] sample state Example 1 Ungelled Example 2 Slightly gelled, can be dispersed by stirring Example 3 Store at room temperature for 7 days, jelly-like
[0113] Table 3
[0114] Sample number abbreviation Force value kN / m R RC M CP TR Application Example 1-1 19.85 100 0 0 0 0 Application Examples 1-2 19.89 100 0 0 0 0 Application Examples 1-3 18.78 100 0 0 0 0 Application Examples 1-4 19.58 100 0 0 0 0 Application Example 2-1 21.58 100 0 0 0 0 Application Example 2-2 20.33 100 0 0 0 0 Application Examples 2-3 21.59 100 0 0 0 0 Application Examples 2-4 21.81 100 0 0 0 0 Application Example 1-1 Aging 17.95 100 0 0 0 0 Application Example 1-2 Aging 18.02 100 0 0 0 0 Application Examples 1-3 Aging 17.38 100 0 0 0 0 Application Examples 1-4 Aging 17.59 100 0 0 0 0 Application Example 2-1 Aging 16.89 100 0 0 0 0 Application Example 2-2 Aging 16.55 100 0 0 0 0 Application Example 2-3 Aging 16.68 100 0 0 0 0 Application Example 2-4 Aging 16.48 100 0 0 0 0
[0115] The failure reading is based on 100% retention of rubber on the substrate and only describes numbers, such as 100, the adhesion rate R (rubber) ≈ 100-M-RC-CP, TR (thinner rubber) is generally not considered to be bonded in this industry.
[0116] It can be seen from Table 3 that the adhesive in Application Example 1 after aging has no obvious gelation, and Application Example 2 has slight gelation, which shows that the amount of surfactant has an impact on its coating result. Insufficient surfactant is not enough to form microcapsules, resulting in some materials being exposed and partially inactivated, resulting in gelation, while Application Example 1 is completely coated; and Application Example 3 has become jelly-like, indicating that the molecular chain has formed a three-dimensional structure, and the solvent is wrapped in the polymer chain to form a gel, which can no longer be dispersed, indicating that the coating is effective and microencapsulation is an effective treatment method.
Claims
1. A heat-vulcanized adhesive containing a microcapsule structure, characterized in that: The raw materials for preparation include, by weight percentage: 2-15% halogen-containing polymer, 1-10% vulcanizing agent, 1-10% nitrogen-containing prepolymer, 1-10% reinforcing agent, 1-10% filler, 0.01-2% microcapsule packaging material, and xylene is supplemented to 100%.
2. The heat-vulcanized adhesive containing a microcapsule structure according to claim 1, characterized in that: The microcapsule packaging material comprises an aqueous phase and an organic phase, and the weight ratio of the aqueous phase to the organic phase is (1-2): (1-2).
3. The heat-vulcanized adhesive containing a microcapsule structure according to claim 2, characterized in that: The raw materials for preparing the water phase include water, a dispersant and a nitrogen curing agent. The dispersant accounts for 2%-5% of the mass of water, and the nitrogen curing agent accounts for 0.02-2% of the total mass of the heat-cured adhesive.
4. The heat-vulcanized adhesive containing a microcapsule structure according to claim 3, characterized in that: The HLB value of the dispersant is greater than 10, and the dispersant is selected from a nonionic dispersant, an anionic dispersant, or a combination of both.
5. The heat-vulcanized adhesive containing a microcapsule structure according to claim 4, characterized in that: The dispersant is a combination of a nonionic dispersant and an anionic dispersant, and the weight ratio of the nonionic dispersant to the anionic dispersant is (0.4-0.9):0.
1.
6. The heat-vulcanized adhesive containing a microcapsule structure according to claim 3, characterized in that: The raw materials for preparing the organic phase include organic solvent, microcapsule wall material, thermal initiator and photoinitiator, and the microcapsule wall material accounts for 2%-5% of the mass of the organic solvent.
7. The heat-vulcanized adhesive containing a microcapsule structure according to claim 6, characterized in that: The microcapsule wall material is selected from one or a combination of methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methylpropionate, butyl methylpropionate, styrene, dimethyl carbonate, and methacrylic acid.
8. The heat-vulcanized adhesive containing a microcapsule structure according to claim 1, characterized in that: The halogen-containing polymer is a halogenated rubber, and the halogenated rubber is selected from one or a combination of chlorosulfonated polyethylene, chlorinated natural rubber, chlorinated polypropylene, maleic anhydride-modified chlorinated polypropylene, epoxy resin-modified chlorinated polypropylene, chlorinated ethylene-vinyl acetate copolymer, and chlorinated polyethylene.
9. A method for preparing a heat-vulcanized adhesive containing a microcapsule structure according to any one of claims 6 to 8, characterized in that: The following steps are involved: S1 weighs the crushed halogen polymer and dissolves it in xylene to form a glue solution for later use; S2 weighs the vulcanizing agent, nitrogen-containing prepolymer, reinforcing agent, and filler and disperses them in xylene, then adds the prepared adhesive solution, stirs and disperses them in a stainless steel container, and then grinds them with a sand mill to control the fineness, discharges the material, obtains a mother liquor, and sets it aside; S3: adding a dispersant and a nitrogen curing agent to water, dispersing and dissolving them to obtain a water phase; adding a wall material, a thermal initiator and a photoinitiator to an organic solvent, dispersing and dissolving them to obtain an organic phase; S4: gradually drop the organic phase into the aqueous phase, emulsify while stirring, initiate polymerization using a light curing machine after the dropwise addition, precipitate a white precipitate after irradiation, centrifuge, wash, dry, and sieve to obtain a microcapsule structure; S5: dispersing the microcapsule structure into the mother solution prepared in step S2, adding xylene, and dispersing the microcapsule structure uniformly.
10. The method for preparing the heat-vulcanized adhesive containing a microcapsule structure according to claim 9, characterized in that: The total grinding time in step S2 is 30-60 minutes, the grinding times are 2-3 times, and the fineness of the mother liquor is ≤45 μm.
